2010
DOI: 10.1021/ja1044192
|View full text |Cite
|
Sign up to set email alerts
|

Superresolution Imaging of Targeted Proteins in Fixed and Living Cells Using Photoactivatable Organic Fluorophores

Abstract: Superresolution imaging techniques based on sequential imaging of sparse subsets of single molecules require fluorophores whose emission can be photoactivated or photoswitched. Because typical organic fluorophores can emit significantly more photons than average fluorescent proteins, organic fluorophores have a potential advantage in superresolution imaging schemes, but targeting to specific cellular proteins must be provided. We report the design and application of HaloTag-based target-specific azido DCDHFs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(164 citation statements)
references
References 29 publications
4
159
0
1
Order By: Relevance
“…Chemical tags have been used to study the localization and dynamics of proteins in living cells, especially in experiments that can not be easily performed with fluorescent proteins. In the last few years, chemical tags have been used to label proteins with fluorophores suited for advanced imaging technologies such as super-resolution (SR) microscopy [57][58][59], Ca 2ĂŸ -imaging [60][61][62], pH sensing [63], hydrogen peroxide detection [64], chromophore assisted light inactivation [36,65,66], and multi-photon microscopy [19]. Recently, Kosaka et al demonstrated the use of the Halo-tag to perform in vivo imaging studies in live animals for the first time [67].…”
Section: Applications Of Chemical Tags In Live Cell Imagingmentioning
confidence: 99%
“…Chemical tags have been used to study the localization and dynamics of proteins in living cells, especially in experiments that can not be easily performed with fluorescent proteins. In the last few years, chemical tags have been used to label proteins with fluorophores suited for advanced imaging technologies such as super-resolution (SR) microscopy [57][58][59], Ca 2ĂŸ -imaging [60][61][62], pH sensing [63], hydrogen peroxide detection [64], chromophore assisted light inactivation [36,65,66], and multi-photon microscopy [19]. Recently, Kosaka et al demonstrated the use of the Halo-tag to perform in vivo imaging studies in live animals for the first time [67].…”
Section: Applications Of Chemical Tags In Live Cell Imagingmentioning
confidence: 99%
“…[1][2][3] The power of such imaging methods has led to increased interest in identifying new types of dyes, opticallyactive materials, and nanoparticles that have enhanced photophysical properties suitable for multimodal, multiplexed, and super-resolution imaging. [4][5][6][7][8][9][10][11][12][13][14] Because fluorophores play such a critical role in understanding biological processes, it is somewhat surprising that most advances in small molecule dye technology today rely on structural modifications of scaffolds discovered over a century ago. [15] For example, the robust Janelia FluorÒ and some AlexaFluorÒ dyes are structurally modified versions of rhodamine scaffolds discovered 130 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…However, these improvements came at the expense of ease of intracellular labelling. Intracellular labelling with organic fluorophores in living cells can be achieved using genetically encoded tags such as SNAP or HaLo tag as previously demonstrated for live-cell super-resolution imaging of bacterial proteins or histone proteins in mammalian cells [50,51] . These tags react with a small peptide, which contains an organic fluorophore as a label.…”
Section: Localization Based Methods -Storm/palm/fpalmmentioning
confidence: 99%